Blueprint: Zauber presser / Anis Suhaila Razman, Mardhiah Mat Din … [et al.] - Razman, Anis Suhaila; Mat Din, Mardhiah; Tawfik Teow, Muhammad Aidil; Sabri, Nor Farahin (2018)
The purpose of the product development are to optimize the recommended dose of daily micronutrients consumption among customers. To provide the suitable juice combination concerning the customers' current health condition.